Genome-Wide Association Analysis for Salt–Induced Phenotypic and Physiologic Responses in Rice at Seedling and Reproductive Stages - Chen, Gang; Hu, Keming; Zhao, Jianhua; Guo, Feifei; Shan, Wenfeng; Jiang, Qiuqing; Zhang, Jinqiao; Guo, Zilong; Feng, Zhiming; Chen, Zongxiang; Wu, Xiaoxia; Zhang, Shengwei; et al. (Frontiers in Plant Science, 2022)
Salinity is one of the main adverse environmental factors severely inhibiting rice growth and decreasing grain productivity. Developing rice varieties with salt tolerance (ST) is one of the most economical approaches to cope with salinity stress. In this study, the salt tolerance of 220 rice accessions from rice diversity panel l (RDP1), representing five subpopulations, were evaluated based on 16 ST indices at both seedling and reproductive stages under salt stress. An apparent inconsistency was found for ST between the two stages. Through a gene-based / tightly linked genome-wide association study with 201332 SNPs located within genes and their flanking regions were used, a total of 214 single nucleotide polymorphisms (SNPs) related to 251 genes, significantly associated with 16 ST-related indices, were detected at both stages. Eighty-two SNPs with low frequency favorable (LFF) alleles in the population were proposed to hold high breeding potential in improving rice ST. Fifty-four rice accessions collectively containing all these LFF alleles were identified as donors of these alleles. Through the integration of meta-QTL for ST and the response patterns of differential expression genes to salt stress, thirty-eight candidate genes were suggested to be involved in the regulation of rice ST. In total, the present study provides valuable information for further characterizing ST-related genes and for breeding ST varieties across whole developmental stages through marker-assisted selection (MAS).